Anger, Anger Expression Types, Problem Behaviors, and Suicide Probability in Adolescent Women using Cluster Analysis - So Hyun Moon; Hun Ha Cho (Korean Society of Women Health Nursing, 2015)
PURPOSE: This cross-sectional study was designed to identify anger-expression types of adolescent women and investigate the relationship between the identified anger-expression types and their problem behaviors and suicide probability. METHODS: The participants were 942 students at two female high school located in Gwangju. The data were analyzed using descriptive statistics, cluster analysis, t-test, ANOVA, and Scheffe multiple comparison test. RESULTS: Cluster analysis revealed 4 distinct anger expression types; Anger-out, Low anger expression, Anger-control, and Anger-in/out types. Female adolescent women had a higher level of trait anger or who frequently used the anger-in/out type reported internalized-externalized problem behaviors and suicide probability more frequently compared to those who frequently used the other three types of anger expression. CONCLUSION: Female adolescent women who had the low anger expression type and anger control type managed anger most effectively. The findings suggest the necessity of a development of the program for lowering the trait anger level and controlling the unfavorable anger expression types such as the anger-in/out.